Mode-Locked CO Laser for Isotope Separation of Uranium Employing Condensation Repression. (28th November 2010) - Baranov, Igor Y.; Koptev, Andrey V.
Abstract : In the present work, we have suggested a technical solution of a CO laser facility for industrial separation of uranium used in the production of fuel for nuclear power plants. There has been used a method of laser isotope separation of uranium, employing condensation repression in a free jet. The laser operation with nanosecond pulse irradiation can provide acceptable efficiency in the separating unit and the high effective coefficient of the laser with the wavelength of 5.3 μ m. Receiving a uniform RF discharge under medium pressure and high Mach numbers in the gas stream solves the problem of an electron beam and cryogenic cooler of CO lasers. The laser active medium is being cooled while it is expanding in the nozzle; a low-current RF discharge is similar to a non-self-sustained discharge. In the present work, we have developed a calculation model of optimization and have defined the parameters of a mode-locked CO laser with an RF discharge in the supersonic stream. The CO laser average power of 3 kW is sufficient for efficient industrial isotope separation of uranium at one facility.